Biological removal of colour from textile finishing washwater - Rakmi A. Rahman ,; Mohd. Ariffin Aton, (1989)
Most dyes are by nature recalcitrant. An initial dye biodegradation study indicates that given the right process conditions, colour due to azo dyes can be removed biologically from wastewater. Biodegradation has been found to proceed via cleavage of azo bond(s). Anoxic condition was found to be necessary for biological colour removal. The removal rate was faster in the presence of a readily biodegradable co-substrate